Analisis Pencahayaan Ruang Kerja: Studi Kasus Pada Usaha Kecil Mikro dan Menengah (UMKM) Batik Tulis di Yogyakarta - Dwi Handayani; Lina D. Fathimahhayati; Suhendrianto Suhendrianto; Selly Pinangki; I.G.B. Budi Dharma (Dinamika Rekayasa, 2013)
A good workspace significantly affects on work productivity. Therefore, in designing a workspace, it is necessary to put much concern on lighting condition. A good condition on it can make workers comfortable during their activities and further increase productivity.This research shows data taken from real-lighting condition in small-medium handmade Batik industry,namely Batik Sogan which is located in Yogyakarta. The object of this research is a workspace with some working activities for example sewing, over edge sewing, and buttons attachment. With Dialux 4.8 software, the research is conducted to compare between direct measurement and lighting simulation result, as well as giving recommendation to improve lighting condition which fits in standards. The result shows that the lighting condition in Sewing-room in Batik Sogan is below standard, i.e., 91 – 125 lux. Therefore, sewing-room condition must be improved, so that the lighting condition may meet the standardized lighting for working conditions which is 500-1000 lux. Simple and cheap improvement to it are to replace the type of the lamp into Philips 4MX091 TL as many as 4 items and to change the colour of the rooms and the desks into white, so it can achieve the maximum lighting 693 lux, which has met the minimum standards for rather- soft working lighting.